Potent Antiproliferative Effect on Liver Cancer of Medicinal Plants Selected from the Thai/Lanna Medicinal Plant Recipe Database "MANOSROI III" - Aranya Manosroi (2018)
© 2015 Aranya Manosroi et al. Thai/Lanna medicinal plant recipes have been used for the treatment of several diseases including liver cancer. In this study, methanolic extracts (MEs) of 23 plants were tested for antiproliferative activity on human hepatoma cell line (Hep G2) by the sulforhodamine B (SRB) assay. Nine MEs with potent antiproliferative activity (IC50< 100 μg/mL) were obtained and further semipurified by liquid/liquid partition extraction. The semipurified fractions were tested for the antiproliferative and antioxidative activities. ME of Stemona collinsae and the semipurified extract and methanol-water fraction (MF) of Gloriosa superba gave the highest antiproliferative activity on HepG2 which were 4.79- and 50.07-fold cisplatin, respectively. The semipurified fractions showed an increased antiproliferative activity. MF of Caesalpinia sappan and HF of Senna alata showed the highest free radical scavenging and metal chelating activities, respectively. The compound in n-hexane fraction (HF) of Ventilago denticulata which showed an increase in antiproliferative activity comparing to its ME was isolated and identified as emodin. This study has demonstrated the potential of the ME from S. collinsae, MF from G. superba, and emodin isolated from V. denticulata, for further development as an antiliver cancer agent.